Preventing secondary exposure to women from men applying a novel nestorone/testosterone contraceptive gel. (16th December 2018) - Yuen, F.; Wu, S.; Thirumalai, A.; Swerdloff, R. S.; Page, S. T.; Liu, P. Y.; Dart, C.; Wu, H.; Blithe, D. L.; Sitruk‐Ware, R.; Long, J.; Bai, F.; et al.
Abstract: Background: Testosterone (T)/Nestorone (NES) combination gel is a potential transdermal male contraceptive that suppresses gonadotropins and spermatogenesis. Transfer of transdermal T from men to women can be prevented by washing or covering application sites with clothing. Objectives: We hypothesized that showering or wearing a shirt over gel application sites would prevent secondary exposure of T and NES to a woman after close skin contact. Materials and methods: Twelve healthy male and 12 healthy female participants were recruited. Men applied T/NES 62 mg/8 mg gel to their shoulders and upper arms. Two hours after application, female partners rubbed the application site for 15 min. Exposure in the female partner was assessed under three conditions: a shirt covered the application site; the man showered prior to skin contact; or without intervention to reduce transfer. Serum T and NES concentrations were measured by LC‐MS/MS in serial blood samples for 24 h after gel exposure. Main Outcomes: Change in female serum T and NES levels as measured by average concentration over 24 h (Cavg ). Results: Median female serum T Cavg was 23.9 ng/dL (interquartile range, 19.3, 33.9) with the shirt barrier and 26.7 ng/dL (20.7, 33.9) after showering, which was higher than baseline 20.9 ng/dL (16.7, 25.0), both p  < 0.03) but lower than without intervention (58.2 ng/dL [30.9, 89.1], both p  < 0.01). Female serum NES Cavg and maximum concentration were below the lower limit of quantification with the shirt barrier and after showering, but increased without intervention in six of 12 women (maximum concentration <60 pg/mL). Men had lower average serum NES levels after showering (47 pg/ml [20, 94] compared to no intervention (153.3 pg/mL [51, 241], p  < 0.02). Conclusion: Secondary transfer of T and NES occurs after intensive skin contact with the gel application site. Secondary transfer is decreased by a shirt barrier or showering before contact.